Pengaruh Motivasi Kualitas, Karier, Ekonomi dan Sosial Terhadap Minat Mahasiswa Akuntansi Mengikuti Pendidikan Profesi Akuntansi (PPA/PPAk.) - Mardi Mardi; Herni Kurniawati (Jurnal Keuangan dan Perbankan, 2014)
This study attempts to examine whether the quality of motivation, career, economic, and social influence on student interest in accounting FE UNJ follow the Accounting Profession (PPA/ PPAk.). The data used in this study is primary data obtained from a questionnaire research instruments were given to FE students UNJ Accounting Department. It can be concluded that this study used a survey method with the selection of the samples tested in this study using purposive sampling method. Of the 200 questionnaires distributed, the number of questionnaires returned and deserve to be processed by 111 questionnaires. Data using multiple regression analysis to answer the research hypothesis with the software PASW Statistics 18 and Eviews 6. The method used is multiple regression analysis.The results of this study were (1) Motivation Quality has a positive influence on student interest in accounting FE UNJ follow PPA/ PPAk , (2) Career Motivation in this study had no effect on student interest in accounting FE UNJ follow the Accounting Profession PPA/ PPAk., (3) Economic Motivation has a positive influence on student interest in accounting FE UNJ follow PPA / PPAk , (4) Social Motivation has a negative influence on student interest in accounting FE UNJ follow PPA/ PPAk., (5) Quality Motivation, Career Motivation, Motivation Economic and Social Motivation together simultaneously influencing accounting student Interests FE UNJ follow PPA / PPAk